Application of the Case Based Learning (CBR) Method to Diagnose Conjunctivitis - Ramadhani, Marco; Volvo Sihombing; Gomal Juni Yanris (Politeknik Ganesha Medan, 2021)
Conjunctivitis is an inflammation of the conjunctiva or the outer layer of the eye and the inner lining of the eyelids caused by micro-organisms or viruses, bacteria, fungi, chlamydia, allergies, irritation of chemicals. The problems that arise start from common symptoms that are often shown or are shown by eye diseases such as redness of the eye area and then cause pain and soreness. Diagnosis can be made by an ophthalmologist. In addition, to diagnose eye diseases, an expert system can also be used to pour expert knowledge into an expert system, thus helping diagnose eye diseases. The research objective is to analyze a desktop-based expert system program that contains the knowledge of a trusted expert/doctor who has the ability to be able to diagnose the disease from the eye disease symptoms felt by the patient quickly and precisely. The stages of research carried out in this study include literature study, data collection, system design, system creation, system testing. In addition, the authors developed using the Case-Based Reasoning (CBR) method, which is one method of building an expert system by making decisions from cases with the solution of previous cases to determine the type of conjunctivitis.